Pulmonary function tests and their associated factors in people living with HIV at Jimma medical center; Ethiopia: a comparative cross-sectional study - Azezew, Muluken Teshome; Gobena, Teshome; Mengstie, Misganaw Asmamaw; Mulat, Elias (Frontiers in Reproductive Health, 2023)
Background- People living with HIV (PLHIV) have a greater risk of developing respiratory disorders. The problems are linked to poor socio-economic status, high viral load, low CD4 counts, and anti-retroviral therapy. Despite the high prevalence of respiratory disorder, the association between HIV infection and pulmonary function status and their associated factors have not yet been well established in resource-scarce countries. Methods: A comparative cross-sectional study was conducted from September 24 to October 15 of 2020 at Jimma Medical Center among people living with HIV, and age-sex matched comparison group. Data were collected using a pretested structured questionnaire administered via face-to-face interview. The collected data included socio-demographic, respiratory, HIV infection, and substance use related. Pulmonary function tests were conducted using SP10 spirometer. Collected data were entered and analyzed using SPSS version 26. Independent t-test and multiple linear regressions were carried out to identify factors associated with the pulmonary function status of the study participants. Results: Ninety-six PLHIV and ninety-six matched control individuals participated in the study. A mean of pulmonary function test parameters among PLHIV respondents was FVC (l) (67.35±19.12, p0.003), FEV1s (l) (61.76±16.04, p0.001), and PEFR (50.14±23.32, p0.001) with a significant lowering in the study group. Female sex, respiratory symptom, duration of HIV, duration of treatment, and khat chewing were associated with lowered FEV1s (l) (p<0.05) in HIV-positive respondents. Conclusion: PLHIV had significantly lower mean lung function parameters than HIV-uninfected participants. As a result, health providers should screen HIV-positive patients with respiratory symptoms, prolonged duration of HIV infection, prolonged treatment, and khat chewing for non-infectious lung disorders while treating PLHIV patients.